ANALYSIS OF EXPORT COMPETITIVENESS TEXTILE AND APPAREL INDONESIA, CHINA, INDIA - Susanto, Bambang; Sukadwilinda (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The textile and apparel industries are labor-intensive and capital-intensive industries. The focus of this research looks at the competitiveness of textiles and apparel in Indonesia, China and India. The research method used is comparative descriptive, with the Herfindahl approach, Trade Specialization, Relevealed Comparative Adventage and Constan Market Share. Herfindahl calculation shows the market structure in Indonesia, China and India in the form of perfect competition. While the Trade Specialization approach, Indian exports are more stable than Indonesia and China. The TSR approach generally shows Export Promotion. The Revealed Comparative Adventage approach, Indonesia and India show stable and stagnant results, the RCA scale shows that China has a comparative advantage and strong competitiveness. Conclusion of the research, the market structure takes the form of a perfect competition and Export Promotion. China Has comparative advantages and strong competitiveness, followed by Indonesia and India.